Mythologism in modern Uzbek prose - Dr. Manzura Otajanova (Genius Journals, 2022)
In this article, by the example of the analysis of mythologisms in modern Uzbek prose, the relationship between folklore and written literature, functional and semantic features of ancient mythological plots and images are revealed. The writer creators that the mythopoetic interpretation is a peculiar feature of modern Uzbek prose.
Keywords: folklore; motive; myth; mithologizm